Flow cell within an LED: a proposal for an optical absorption detector - Ugucione, Cassia; Cardoso, Arnaldo Alves [UNESP] (Springer, 2007)
Droplets formed at the tip of a tube under the same conditions possess extreme uniformity of form, volume and weight. These properties of liquid drop formation have been known for a long time and consequently many applications for the drop have been found in instrumentation and chemical analysis methods. In the present paper, we report on the analytical use of a dynamic LED-based flow-through optical absorption detector with optical path length controlled by continuous dropping of a solution. This arrangement consists of a flow cell built within a high-intensity red LED (lambda (max)=630 nm). The feasibility of the detector is demonstrated by colorimetric determination of methylene blue, and ammonium by Berthelot's reaction, in a flow-injection system. For ammonium, the reaction forms a blue dye (indophenol) with a maximum absorption at 630-650 nm. The detection limit, considered as 3 times the signal of the blank, is better than 125 mu g l(-1). The small flow cell represents a good combination of optical path length, low volume and fast washout. This detector can be used advantageously in automated methods and can represent a solution to problems of optical detection involving gas bubbles and precipitation of particles in turbidimetric applications.
Keywords: LED-based detector; optical absorption detector; flow cell; ammonium determination